Stress in pacu exposed to ammonia in water - Abreu, Janessa Sampaio de [UNESP]; Esteves, Fábio Resende [UNESP]; Urbinati, Elisabeth Criscuolo [UNESP] (Sociedade Brasileira de Zootecnia, 2012)
The present study evaluated stress indicators in pacu exposed to ammonia in water under the following conditions: without NH4Cl (0.00 g/L); with 0.0078 g NH4Cl/L; and with 0.078 g NH4Cl/L (pH 8.3 and 27 ºC). After the salt dilution the water flow was interrupted and reestablished in 24 hours. Sampling occurred prior to the addition of NH4Cl (control) and after 12, 24 and 48 hours. Glycaemia increased only in fish with the highest salt concentration when compared with group control, regardless of time, and at 24 hours, regardless of treatment. Plasma ammonia, highest in fish exposed to the highest NH4Cl concentration, decreased progressively up to 48 hours. Plasma chloride only decreased in fish not exposed to salt when compared with control and osmolality increased after 24 hours. Hematocrit (Ht), number and volume of erythrocytes and hemoglobin did not change when NH4Cl was added; Ht decrease was reported after 12 hours, but it was not followed by the other blood parameters. The results show tolerance of the pacu to ammonia in the environment.
Keywords: cortisol; fish farming; fish physiology; Piaractus mesopotamicus; plasmatic ammonia; water quality